Customization Of Requirements Modeling Tool For Software Engineering Education - Syed Ahmad, Sharifah Sakinah; Kamalrudin, Massila; Sidek, Safiah (2014)
Requirements modelling tools readily available in the market have been conveniently used as teaching and learning tools in the teaching of software engineering (SE) subjects. Students are expected to gain the skills of eliciting, analyzing, specifying and validating requirements as they use the requirements modelling tools in class. However, these tools are mainly developed for industry purposes; hence they are not suitable for teaching and learning due to their high cost and complexity. This paper reports a study that develops an approach and supporting tool that customize the requirements modeling tool for SE learning purposes. The main objectives of this work are twofold: 1) to assist the learning process of the students to model the use diagram, and 2) to understand the syntax of the use case diagram. A requirements modeling tool, named CustomTool, which is customized for SE education has been developed, and it was tested for its effectiveness and usability using questionnaire survey. Based on the survey results, it can be concluded that users particularly students were satisfied and comfortable using the tool in the classroom.